To deconstruct or how to deconstruct?: A Presbyterian perspective, 1960–1990 - Duncan, Graham (HTS teologiese studies, 2017)
The art of deconstruction is a process that aims to lead to the truth; the truth regarding apartheid in South Africa is contested. Presbyterian historiography regarding apartheid has lacked clarity because of a lack of reliable sources. This article seeks to elucidate greater clarity by interrogating one source written from within the Presbyterian Church of Southern Africa dealing with the period, 1960–1990.